Occupational Stress, Social Support, and The Costs of Health Care - Manning, Michael R.; Jackson, Conrad N.; Fusilier, Marcelline (Academy of Management Journal, 1996)
Relationships among health care costs, social support, and occupational stress are investigated. Health care cost data were collected over two years for 260 working individuals. Multiple regression analyses were used to control for initial health care costs, age, and gender in predicting later costs; independent variables were stress, strain, social support, and their interactions. Main effects and interactions each accounted for significant proportions of the variance in various health care costs.